Application of the General Clause of Reasonableness and Criterion of Rationality in Polish Tax Law - Münnich, Monika (Review of European and Comparative Law, 2020)
This paper’s objective is to present two methods of introducing elements of the civil general clause of reasonableness into tax law. One of them is the lawmaking process, the other is the application of law, i.e. the decisions of tax authorities and the jurisprudence of national administrative courts.